1998
DOI: 10.1159/000009952
|View full text |Cite
|
Sign up to set email alerts
|

Childbirth as a Biological Model for Stress?

Abstract: Objective: The aims of this investigation were to measure corticotropin-releasing hormone (CRH), corticotropin (ACTH) and cortisol before, during and after delivery searching for an endocrine intercorrelation of the hypothalamic-pituitary-adrenal (HPA) axis and to correlate these findings with obstetrical variables. Methods: Blood was sampled from 50 women with singleton pregnancies at term without uterine contractions, during delivery (after full cervical dilatation) and on the 4th postnatal day. Hormones wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Studies in humans have shown that maternal glucocorticoids after birth are reduced to their previous state within 4 days (Bergant et al, 1998). According to our results, in domestic kittens, a decrease in the percentage of neutrophils and an increase in the proportion/ number of lymphocytes ended in the first month of life.…”
Section: Effect Of Agesupporting
confidence: 70%
See 1 more Smart Citation
“…Studies in humans have shown that maternal glucocorticoids after birth are reduced to their previous state within 4 days (Bergant et al, 1998). According to our results, in domestic kittens, a decrease in the percentage of neutrophils and an increase in the proportion/ number of lymphocytes ended in the first month of life.…”
Section: Effect Of Agesupporting
confidence: 70%
“…The number of leukocytes and neutrophils in kittens in the first day after birth (white-single paternity; grey-multiple paternity) adrenocorticotropic hormone (Alehagen et al, 2005;Bergant et al, 1998). In cows, a few days before calving, the number of neutrophils in the blood increases by 2-3 times; a similar picture is observed in newborn calves (Simonyan and Khisamutdinov 1995).…”
Section: Effect Of Agementioning
confidence: 88%
“…Yet, unlike the strong association of ACTH to cortisol in nonpregnant women, the relationship of ACTH to cortisol in labor and the stress of labor are unclear. Although data are limited, in one study ( N = 28), investigators found no correlation between ACTH and cortisol levels during labor (Odagiri et al, 1982), while in a second study there was a weak positive correlation ( r = .37, N = 50) between ACTH and cortisol levels (Bergant et al, 1998). However, variables such as the point in labor when data were collected were not consistent between these two studies.…”
Section: Hpa Axis During Late Pregnancy and Labormentioning
confidence: 99%